‘Off with their heads!’ The imagery of the head in the trilogy of Psalms 108-110 (Part 1) - Sutton, Lodewyk (Stellenbosch theological journal, 2017)
A social-scientific analysis of the word ‘head’ in Psalms 108-110 indicates from another theme (war) and perspective (honour), how the imagery of the head communicates warfare, develops and establishes a connection between Psalms 108-110. In this two-part article, this is established by indicating in the first article that the imagery of the head can be considered as part of warfare imagery. The value system of honour and shame as expressions of the function and purpose of the warfare imagery is made through a social-scientific analysis of the head. The iconography of different ancient Near Eastern contexts is used as an extra-textual source to elucidate the concept of the head as an aspect of warfare imagery, expressed through honour and shame. Part two (the second article) of this article examines and applies the use of the imagery of the head in Psalms 108-110 by integrating the deductions made in this first part of this article. This helps to indicate the development and connection between Psalms 108-110 through the imagery of the head.